KEADILAN GENDER DALAM RANCANGAN QANUN HUKUM KELUARGA - Muhammad Ridwansyah (Jurnal Hukum Samudra Keadilan, 2019)
This article wants to highlight the theory of gender justice in the draf Family Law Qanun, does the DPRA and the Aceh Government accommodate the theory or even omission?. Then from behind the theory of gender justice there is the essence of gender justice that should be applied in the a quo qanun design? Gender justice itself should be interpreted as equal treatment and not discriminated based on their natural identity. If so, that women are also understood or interpreted to be able to be married to more than one person? There are two results of this study as follows: First, the theory of gender justice is not accommodated at all in the draf Family Law Qanun, so it is feared that women’s rights will be violated by the qanun a quo. The arrangement of polygamy in the design of the a quo qanun in fact missed the theory of gender justice. Evan the principle of justice is not given space in the articles on polygamy, tends to regulate procedurally. Second, the nature of the theory of gender justice is not touched by the Family Law Qanun Formulation Team, so that it can be ascertained that after the establishment of the a quo qanun there will be a degradation of Acehnese female figure. Then Aceh became the center of decline in terms of attitudes towards women. Indeed, this must be understood that ancient Aceh placed women in a respectable position.